Vicente Chávez, esclavo: un caso de "sujeto en justicia". Santiago de Chile, 1703 - Katherine Quinteros (Nuevo mundo - Mundos Nuevos, 2012)
The document presented is preserved in the National Archives History of Chile, is a civil case that stands Vincent Chaves, brown slave of Joseph of Montenegro. On the record, Vincent tells us that Ventura sues teacher Sastre, who had a store in the plaza of the city of Santiago and Pedro de la Rosa Sastre free mulatto officer of Ventura. Master and generate a scuffle with officer Vincent who also publicly insult. And at the same time insult to the legitimate wife of Vincent - Ursula india - which also received blows consideration. The exposure of this case allows us to approach the judicial area, to see through this universe of records that is patented polyvocal in writing. The dialogue established between the involved and the complexities of actual registration.